2020
DOI: 10.21203/rs.3.rs-60569/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Health Related Quality of Life Among Heart Failure Patients Attending an Outpatient Clinic at University of Gondar Comprehensive Specialized Hospital Northwest Ethiopia 2020: Structural Equation Modeling Approach

Abstract: Background: Chronic heart failure (CHF) is one of the most important public health concerns in the industrialized and developing world having increasing incidence and prevalence. Measuring quality of life using rigorous statistical method may be helpful to provide input for decision makers, policy makers and development of guidelines for the Ethiopia. The aim of this study was to determine health-related quality of life and its associated factors among heart failure patients attending University of Gondar comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…However, Alla et al [ 42 ] and Scott et al [ 43 ] eventually agreed on a multidimensional account that encompasses the physical, psychological, and social dimensions of HRQoL, all of which are incorporated in the SF-36 health survey [ 33 35 ]. Building on that approach, the present study found higher scores across almost all of the SF-36 domains compared to previous studies in the KSA’s Eastern region [ 26 ], Ethiopia [ 44 ], and Spain [ 18 ], which reported low HRQoL across all domains of the SF-36. This might be explained by methodological differences, variations in the history of comorbidities, duration of heart failure, treatment compliance, and differences in health quality.…”
Section: Discussionsupporting
confidence: 63%
“…However, Alla et al [ 42 ] and Scott et al [ 43 ] eventually agreed on a multidimensional account that encompasses the physical, psychological, and social dimensions of HRQoL, all of which are incorporated in the SF-36 health survey [ 33 35 ]. Building on that approach, the present study found higher scores across almost all of the SF-36 domains compared to previous studies in the KSA’s Eastern region [ 26 ], Ethiopia [ 44 ], and Spain [ 18 ], which reported low HRQoL across all domains of the SF-36. This might be explained by methodological differences, variations in the history of comorbidities, duration of heart failure, treatment compliance, and differences in health quality.…”
Section: Discussionsupporting
confidence: 63%
“…Multiple studies demonstrated that older age had a significant relationship with all areas of quality of life as shown in this study. For instance, Tarekegn, Gezie, Birhan, and Ewnetu (2021) concluded that patients over 60 years of age had worse mental health, physical health, social relationships and environmental health. Pelegrino, Dantas, and Clark (2011) and AbuRuz, Alaloul, Saifan, Masa’Deh, and Abusalem (2016) found a negative significant relationship between age and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…physical, social and symptom domains) compared with lower income. Additionally, Tarekegn et al (2021) reported that lower income and lower education level were associated with poorer quality of life. Asimakopoulou et al (2019) found that the older the age of the patient and the lower levels of education, the lower the quality of life of patients with heart failure.…”
Section: Agjsrmentioning
confidence: 99%
“…The sample size was estimated based on a single population proportion formula ( 30 ), considering a Z -value of 1.96 with a 95% level of confidence and a 5% margin of error. The prevalence (P) for sample size estimation was based on a previous study conducted in Ethiopia using the World Health Organization Quality of Life questionnaire (WHOQoL-BREF) instrument ( 15 ), in which 45.6% of patients with heart failure rated their overall HRQoL as poor. We applied the finite population correction factor formula ( 31 ) for the source population of 5,500 CVD patients, and recruited a total of 360 eligible patients using a consecutive sampling method.…”
Section: Methodsmentioning
confidence: 99%
“…To improve patient outcomes, patient-reported problems must be addressed alongside cardiovascular pharmacotherapy. Previous studies showed that a more active involvement of patient's in disease management can substantially enhance HRQoL ( 15 , 16 ). In LMICs, lower socioeconomic status, low access and high cost of medications could negatively affect HRQoL and treatment satisfaction.…”
Section: Introductionmentioning
confidence: 99%